2017
DOI: 10.1002/chem.201703694
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products from Social Amoebae

Abstract: Natural products are invaluable sources of structural diversity and complexity ideally suited for the development of therapeutic agents. The search for novel bioactive molecules has prompted scientists to explore various ecological niches. Microorganisms have been shown to constitute such an important source. Despite their biosynthetic potential, social amoebae, that is, microorganisms with both a uni- and multicellular lifestyle, are underexplored regarding their secreted secondary metabolome. In this review,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 71 publications
(151 reference statements)
0
13
0
Order By: Relevance
“…However, finding the exact chemoattractants is going to require additional work. Metabolites from amoebae are produced in extremely low quantities, which makes it virtually impossible to do a full structure elucidation via NMR [63]. Due to these difficulties, it is likely that natural products from the social amoebae have to be discovered through heterologous expression of the respective gene clusters [63].…”
Section: Discussionmentioning
confidence: 99%
“…However, finding the exact chemoattractants is going to require additional work. Metabolites from amoebae are produced in extremely low quantities, which makes it virtually impossible to do a full structure elucidation via NMR [63]. Due to these difficulties, it is likely that natural products from the social amoebae have to be discovered through heterologous expression of the respective gene clusters [63].…”
Section: Discussionmentioning
confidence: 99%
“…In analogy, protoillud-7-ene, the product of DpTPS6 and its orthologs, may play a conserved, critical role, such as in regulating multicellular development, while the products of other TPS genes may have group- or species-adaptive functions, such as in chemotaxis 23 , defense 24 , or attracting beneficial organisms 25 . Such functions have been proposed for terpenoids as well as other types of secondary metabolites made by dictyostelid social amoebae 26 . Knowledge of the catalytic activities of individual TPSs and their contribution to the biosynthesis of volatile terpenoids during multicellular development in D .…”
Section: Discussionmentioning
confidence: 99%
“…Among them, four bicyclic pyrrolizidines mainly contribute to the amoebicidala ctivity with an IC 50 of 3-41 mm (pyreudione Ci st he most active compound). [46] Among them, some molecules may be involved in defensem echanisms. These resultsa lso suggested that unknown small molecule(s) produced by amoeba can activate the defense mechanism of Pseudomonas.…”
Section: Secretion Of Metabolites For Preventing Predationmentioning
confidence: 99%
“…As am odel organism, D. discoideum has ar ich geneticp otentialf or SMs biosynthesis (for example, its genome harbors 45 and 11 putative PKS and terpene synthase genes, respectively [45] ), and structurally diverse compounds are gradually isolated from this species. [46] Among them, some molecules may be involved in defensem echanisms. For instance,C hen et al pointedo ut that volatile terpenes secreted by D. discoideum might be involved in repelling nematodes.…”
Section: Secretion Of Metabolites For Preventing Predationmentioning
confidence: 99%